2015
DOI: 10.5507/euj.2015.006
|View full text |Cite
|
Sign up to set email alerts
|

A review of studies using the Körperkoordinationstest für Kinder (KTK)

Abstract: The Körperkoordinationstest für Kinder (KTK) (Kiphard & Schilling, 1974, 2007) is a standardized, norm-referenced measure used by physical therapists and occupational therapists in clinic and school practice settings to evaluate the motor coordination (MC) of 5-to 14-year-old children. To find out for which research purposes the KTK has been used and its reliability and validity, we conducted a systematic review. Searching five databases, we found 46 studies used the KTK over four decades. The KTK was widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
2
44
0
4
Order By: Relevance
“…The typical error of measurement and CV% decreased as the number of trials increased, which revealed better reliability of the coordination tests. Similar results were found for the reliability scores in the coordination test for children (KTK test) in a similar age group; the reliability coefficients ranged from 0.60-0.99 and Cronbach's alpha was 0.95 (12). Moreover, Zuvela, Bozanic and Miletic (32) showed that the fundamental movement skills (FMS) -POLYGON is a reliable, valid instrument for 8-year-old children.…”
Section: Discussionsupporting
confidence: 63%
“…The typical error of measurement and CV% decreased as the number of trials increased, which revealed better reliability of the coordination tests. Similar results were found for the reliability scores in the coordination test for children (KTK test) in a similar age group; the reliability coefficients ranged from 0.60-0.99 and Cronbach's alpha was 0.95 (12). Moreover, Zuvela, Bozanic and Miletic (32) showed that the fundamental movement skills (FMS) -POLYGON is a reliable, valid instrument for 8-year-old children.…”
Section: Discussionsupporting
confidence: 63%
“…On the one hand, research suggests that TGMD-3 is a sports-centric test that uses quality evaluations of LM skills and BS, but lacks balance skills [13]. On the other hand, research suggests that KTK is a non-sports specific assessment tool [13,46] focusing on result-based evaluation of balance and motor skills, but lacks BS. Hence, although these two assessment tools complement each other, an assessment tool should ideally include a whole range of fundamental movement skills, i.e., balance skills, LM skills, and BS.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sum of these latter scores yielded the total sum score for the KTK test. The raw score was used in the present analysis, as recommended [46,47]. The KTK assessment tool is considered to be highly reliable internationally, most likely because it is result-based, with the test-retest reliability coefficient of the total score being 0.97 and the subtests ranging between 0.80 and 0.96 [44].…”
Section: Motor Competencementioning
confidence: 99%
“…Most of the studies assessing the coordination of young athletes used the KTK, a valid test aimed at determining the gross motor coordination in school-aged children [152][153][154]. The ESA team has considered a new test, the "Crunning Test", to assess coordination and various other skill-related components of physical fitness.…”
Section: Discussionmentioning
confidence: 99%